Effect of Osmotic Dehydration on Characteristics and Physicochemical Properties of Plant-Based Crisps with Vacuum Fryer - Sirilert , Tunyaporn; Silalai, Nattiga (Burapha Science Journal, 2026)
Background and Objectives : Almost fried products contain high amount of oil since there was an exchange between water in food and oil during frying. Dehydration is one of the methods can reduce moisture content in food products leading to a reduction of oil uptake in fried products. Moreover, vacuum frying can also reduce the amount of oil content in fried food compared to atmospheric frying. Due to the fact that water evaporation under the vacuum condition, there was low excessive retention of oil inside the product. In addition, temperature also affects to product characteristics. Around the glass transition, molecular mobility of food molecules increases resulting in softer product and enhancement of water molecular movement. Objective of the research was; therefore, to study the effect of a pre-treatment method on characteristics of plant-based crisps using osmosis dehydration (OD) prior to vacuum frying and to study thermal properties (glass transition temperature and α-relaxation) of plant-based crisps using a Differential Scanning Calorimeter (DSC) and a Dynamic Mechanical Analyzer (DMA), respectively. All data were used to evaluate the correlation of product characteristics, texture and physicochemical properties of plant-based crisps as well as to provide a guideline for application in other fried food industries. Methodology : In the present study, there were 2 treatments consisting of the plant-based products without pre-treatment before frying (Control) and the products with pre-treatment with osmosis dehydration (OD) using 0.5% (w/w) salt solution (NaCl) prior to frying. The 200 g of pre-treatment products prior to frying were poured in the bowl containing 0.5% (w/w) NaCl solution in the ratio of samples to salt solution at 1:10 and soaked at 30°C for 1 hour. Then, the salt solution was drained and the excess water on the products was wiped off by tissue papers. The samples from both treatments were vacuum fried at 13.33 kPa for 3 hours. All vacuum fried products were analyzed as the physicochemical properties including shrinkage ratio, weight loss, hardness using texture analyzer, Tg using Differential Scanning Calorimetry (DSC), and storage modulus (E’) using Dynamic Mechanical Analyzer (DMA). Main Results : Pre-treatment frying method significantly affected characteristics and physicochemical properties of fried products (p≤0.05). Shrinkage ratio, %moisture content, %fat content and texture of the fried product (control) were 2.53±0.15, 6.90±0.49, 4.36±0.18 and 214.96±1.17 N, respectively, which were higher than those of the fried product with OD method. The shrinkage ratio, %moisture content, %fat content and texture of the fried product with OD method were 1.29±0.08, 3.22±0.54, 3.42±0.26 and 115.20±1.20 N, respectively. On the other hand, %weight loss of the fried product (control) was 88.6±0.82, which was lower than that of the fried product with OD method having 93.4±0.51. Moreover, glass transition temperature (Tg) of the fried product with OD method were 41.17±0.58, which were significantly higher than those of the control fried product having 31.14±0.82 (p≤0.05) as a result of water plasticization behavior. Around the glass transition, storage modulus of the fried product (control) decreased dramatically, whereas a slight decrease in the storage modulus was found in the fried product with OD method. With consideration of a change in mechanical properties (storage modulus, ∆E’), we found that the ∆E’ of the fried product with OD method were lower than that of the control fried product. The ∆E’ of the fried product with OD method was 1.51x109, while the ∆E’ of the control fried product was 5.02x109. This was also consistent with a-relaxation as observed from a change in storage modulus around the glass transition. The a-relaxation temperature (Ta) of the fried product with OD method was 60.93±0.88 ºC, which was significantly higher than that of the control (p≤0.05). The Ta of the fried product (control) was 41.13±0.83 ºC. Texture of the fried products with and without OD method was measured as force value. The results indicated that the storage temperature affected a product texture. Force values of the fried products with OD method stored at 35 ºC were around 115 N, whereas force values of the control were approximately 215 N during storage. However, it seems that the force values of the fried products increased with increasing storage temperature. The force values of the fried products ranged from 215 to 250 N at storage temperature of 45 ºC. The results indicated that the ∆E’ had the correlation with changes in texture of the fried product, which were measured by the texture analyzer. Conclusions : The pre-treatment process prior to frying could reduce shrinkage ratio, but increase weight loss of the fried products. Osmosis dehydration method could decrease moisture and fat content in the fried product, and also reduce changes in physicochemical properties during storage. In addition, DSC and DMA that were used to analyze thermal and mechanical properties of the products can be used to evaluate physical properties, such as fragility and crispness of the fried products during storage. The information could be a guideline to determine changes in fried products during process and storage including shelf-life extension.